2001
DOI: 10.1590/s0036-46652001000600007
|View full text |Cite
|
Sign up to set email alerts
|

Human polyclonal anti-hepatitis B surface antigen immunoglobulin reduces the frequency of acute rejection after liver transplantation for chronic hepatitis B

Abstract: SUMMARYBackground: Use of polyclonal anti-hepatitis B surface antigen immunoglobulin (HBIg) has been shown to reduce hepatitis B virus (HBV) recurrence after liver transplantation (LT) and to decrease the frequency of acute cellular rejection (ACR). However, the protective role of HBIg against ACR remains controversial, since HBV infection has been also associated with a lower incidence of ACR. Aim: To assess the relationship between HBIg immunoprophylaxis and the incidence of rejection after LT. Methods: 260 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Our results confirm previous studies that have reported a low incidence of ACR following LT for HBV in the 1980s–90s, although mechanisms for this association have not been fully elucidated [8,10]. Chronic HBV infection is the result of an inadequate immune response towards the virus.…”
Section: Discussionsupporting
confidence: 88%
“…Our results confirm previous studies that have reported a low incidence of ACR following LT for HBV in the 1980s–90s, although mechanisms for this association have not been fully elucidated [8,10]. Chronic HBV infection is the result of an inadequate immune response towards the virus.…”
Section: Discussionsupporting
confidence: 88%
“…Among the 24 patients who had evidence of HCC in the liver at the time of transplant, only 1 patient (4.2%) had established HCC recurrence. The observed rate of liver rejection in the present study (27.7%) is comparable to the rate reported elsewhere for combined NUC and HBIG therapy . Five patients died during the study.…”
Section: Discussionsupporting
confidence: 87%
“…The observed rate of liver rejection in the present study (27.7%) is comparable to the rate reported elsewhere for combined NUC and HBIG therapy. 30 Five patients died during the study. No death was considered related to the study treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether IVIG are effective as prophylaxis for acute rejection after organ transplantation. In support of this possibility, two papers have reported that treatment of liver graft recipients with anti-HBs Ig or anti-CMV Ig protects against acute rejection (7,8), but a study from another liver transplant center failed to confirm this protective action (9).…”
Section: Introductionmentioning
confidence: 99%